Tingkat Pengetahuan terhadap Donor Darah pada Masyarakat Pendonor - Dina Afrianti; Elis Susilawati; Eko Naning Sofyanita (Jaringan Laboratorium Medis, 2022)
Blood donation is an activity to donate blood for transfusion purposes. The number of voluntary blood donors in Indonesia is around 20% of the total production of blood bags per year, the rest is met from replacement donors. People are generally reluctant to donate blood because of fear of pain when blood is drawn using a syringe, fear of running out of blood, resulting in anemia, contracting the disease through blood donors, feeling unwell to donate blood and feeling that it is enough to only donate blood once. This is a factor that causes the limited number of donors due to limited knowledge. Research Objectives: To see an overview of the level of knowledge about blood donors in the community of donors at Pekalongan City. Methods: The type of research used is descriptive quantitative with a cross sectional approach with a questionnaire to determine the level of knowledge of the donor community. Results: Most of the blood donors at the Pekalongan City are Male 73 respondents (73%), the highest percentage aged 17-30 years as many as 54 respondents (54%), high school education, namely as many as 49 respondents (49%). Most of the donor knowledge level is said to be good, namely 88 respondents (88%). Conclusion: Most of the donor community at the Pekalongan City have a good level of knowledge about blood donation.